Barriers to optimal peritoneal dialysis. Issue 6 (13th September 2020) - Finkelstein, Fredric O.
Abstract: Peritoneal dialysis in the United States is underutilized when compared to the experience in other developed countries. The reasons for this are multifactorial and include government regulatory issues, the priority of dialysis facilities, and education and training of nephrology trainees and patients. The challenges to expanding PD in the United States are discussed and strategies to overcome the barriers are outlined.